School grounds soil contamination with heavy metals and arsenic compounds in the city of Vladimir - Selivanov Oleg (E3S Web of Conferences, 2021)
The article presents the content determining results of heavy metals and arsenic in sod-podzolic soils of the school grounds in Vladimir, Vladimir region. According to the accumulation indicator, the accumulation intensity of heavy metals and arsenic in these areas has been determined, which is decreasing in the series of Pb→As→Cu→Zn→Ni. The calculation of the pollutants hazard coefficient showed that their MPC excess decreases in the series of As→Zn→Pb→Cu→Ni. The soil pollution level has been assessed for the school grounds and their ecological situation has been evaluated applying the cumulative indicator of soil pollution with heavy metals and soil pollution index. The values of the soil pollution cumulative indicator of school territories indicate dangerous and moderately dangerous contamination level of the studied soils, and the calculated values of the soil pollution index refer these soils to the category of “contaminated” soils, which poses potential risks for the schoolchildren health.